1999
DOI: 10.1086/314557
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Subtypes Differ in Disease Progression

Abstract: At least 10 different genetic human immunodeficiency virus type 1 (HIV-1) subtypes (A-J) are responsible for the AIDS pandemic. Much of the understanding of HIV-1 disease progression derives from studies in the developed world where HIV infection is almost exclusively subtype B. This has led many to question whether the properties and consequences of HIV-1 infection can be generalized across subtypes that afflict the majority of infected persons in the developing world. From 1985 to 1997, a prospective study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
198
1
10

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(215 citation statements)
references
References 24 publications
(28 reference statements)
2
198
1
10
Order By: Relevance
“…HIV-1 clade C-infected sex workers in Nairobi and Senegal showed higher viral loads 37 and more advanced disease 38 than those with subtype A or D infection. The viral loads in our study were also higher than those reported for Uganda, although we used an older version of the Roche Monitor HIV-1 PCR (1.0 vs. version 1.5 used in the Uganda study).…”
Section: Discussionmentioning
confidence: 89%
“…HIV-1 clade C-infected sex workers in Nairobi and Senegal showed higher viral loads 37 and more advanced disease 38 than those with subtype A or D infection. The viral loads in our study were also higher than those reported for Uganda, although we used an older version of the Roche Monitor HIV-1 PCR (1.0 vs. version 1.5 used in the Uganda study).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, clinical follow-up studies revealed that subtype C-infected individuals might develop AIDS easier than those infected with other subtypes (27). This appears to be derived from biologically different viruses derived from individual subtype such as rapid and high replication rates as well as more efficient transmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…3, similar results were obtained by pLTR-Luc derived from subtype E and C LTR sequences (data not shown). When we constructed the mutant Tat with serine in place of Cys 27 , Cys 30 , Cys 31 , and Cys 34 , it was found that the resultant Tats including C-Tat similarly lost their activities in Jurkat cells (data not shown). Together, these results suggest that the cysteine-rich motif in C-Tat is important for interaction to human cyclin T1.…”
Section: No Involvement Of a Cysteine-rich Motif And 2nd Exon Of Tat mentioning
confidence: 99%
“…Available data from African and Caribbean populations strongly suggest that time to development of clinical outcome, after HIV infection, is significantly compressed compared to US and European populations, and that differences in the health care delivery systems account for only a part of this accelerated disease process. These therapeutic programs and approaches must also be carefully considered and anchored in what is known about the pathogenesis of HIV/AIDS in such populations and not simply the blanket application of known US and Europe therapeutic strategies [43][44][45][46].…”
Section: Opportunities For Successmentioning
confidence: 99%